ANALISA KEBUTUHAN PROGRAM TRAUMA HEALING UNTUK ANAK-ANAK PASCA BENCANA BANJIR DI KECAMATAN SUNGAI PUA TAHUN 2018 : IMPLEMENTASI MANAJEMEN BENCANA - Rahman, Ade (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Sungai Pua sub-district is in mountainous area, at risk for landslide and flood. Recentlythere was a flood so the locals felt anxious, shocked and even traumatized. Trauma tovictims of natural disasters can not be allowed to drag on. In order for disaster victims tocontinue their lives normally, trauma healing is required. The purpose of this research isto know how big the need of children in sub-district of pua river to program of traumahealing after flood disaster. Quantitative research type, the process of collecting data isdone through questionnaire. The sample in the study was taken in total random sampling,and the number was 72 people. The results showed that 30 children (41.7%) neededentertainment as their need to heal themselves from trauma due to flood disaster, then 22children (30.5%) need home visit, 12 children (16,7%) need sharing partners and 8children (11.11%) require health services. It is hoped that with this program, it can reducethe trauma of children in the aftermath of the disaster, and can continue the research byusing the results of this needs analysis to see how effective these programs are.Key Words :Natural disasters, trauma healing, children